Методи підвищення енергоефективності розрядно-імпульсної технології очищення виликів - Назарова, Н.С.; Діордійчук, В.В. (Технічна електродинаміка, 2011)
The model of an energy effect estimation in the pulse-discharge clearing of castings technology is designed. That allows mathematically strictly to compute expectation of a loss function at continuous operation of the installation. The increases of energy effect of the pulse-discharge technology at applying an adaptive control in view water resistivity in the technological tank is counted.